2021
DOI: 10.3390/met11111750
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Description of Duplex Stainless Steels Microstructure Using Selective Etching

Abstract: The properties of duplex stainless steels (DSSs) depend on the ferrite–austenite ratio, on the content of secondary phases and on the contamination with non-metallic inclusions. To assess the quality of DSSs, it is necessary to use an integrated approach which includes controlling for the volume fraction, the morphology and the distribution of all phases and non-metallic inclusions. Samples of several grades of DSSs were obtained using various heat treatments, such as solution annealing and quenching from 1050… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The simplest and most effective method is to use an automatic image analyzer, but this requires obtaining a phase-contrast image. Various authors suggest a variety of etchants [ 31 ], but a later analysis [ 30 ] carried out by our team showed that even the use of electrolytic etching ( Figure 2 a) does not allow sufficient phase contrast to be obtained for automatic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The simplest and most effective method is to use an automatic image analyzer, but this requires obtaining a phase-contrast image. Various authors suggest a variety of etchants [ 31 ], but a later analysis [ 30 ] carried out by our team showed that even the use of electrolytic etching ( Figure 2 a) does not allow sufficient phase contrast to be obtained for automatic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Today, traditional tools for the development of alloys, which are also used to improve the quality of DSSs, include thermodynamic modeling [ 30 ], which has been successfully used for many applications, along with the use of various quantitative methods for structural evaluations to compare simulated and experimental results [ 31 ]. We considered the applicability of these methods to the experimental steels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations